Extracellular Guanosine 5′-Triphosphate Induces Human Muscle Satellite Cells to Release Exosomes Stuffed With Guanosine - Pietrangelo, Tiziana; Di Filippo, Ester S.; Locatelli, Marcello; Piacenza, Francesco; Farina, Marco; Pavoni, Eleonora; Di Donato, Andrea; Innosa, Denise; Provinciali, Mauro; Fulle, Stefania (Frontiers in Pharmacology, 2018)
The extracellular guanosine 5’-triphosphate, GTP, has been demonstrated to be an enhancer of myogenic cell differentiation in a murine cell line, not yet in human muscle cells. Our hypothesis was that GTP could influence also human skeletal muscle regeneration, specifically in the first phases. We tested GTP stimulus on human muscle precursor cells established in culture by human satellite cells derived from Vastus Laterlais of three young male. Our data show that extracellular GTP a) up-regulated miRNA (specifically miR133a and miR133b) and myogenic regulator factor and b) induces human myogenic precursor cells to release exosomes stuffed with guanosine based molecules (mainly guanosine) in the extracellular milieu. We think that probably these exosomes could be addressed to influence by means of their content (mainly guanosine) in paracrine or autocrine manner the surrounding cells and/or at distance other muscles or tissues.